2016
DOI: 10.1007/s13277-016-5328-z
|View full text |Cite
|
Sign up to set email alerts
|

NETs in cancer

Abstract: Many aspects of neutrophil hyperactivity and its role in numerous immune responses still remain a mystery. A new neutrophil mechanism was discovered recently, i.e., the formation of neutrophil extracellular traps (NETs). These structures, composed of DNA strands and neutrophil granule proteins, are an element of the non-specific immune response and bind pathogens to prevent their spread and ensure increased local concentrations of toxic factors. Research on this phenomenon shows that tumor-associated neutrophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
44
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 56 publications
1
44
0
2
Order By: Relevance
“…Thereafter, cytoplasmic granules in the neutrophil get fused with the phagolysosome where the microorganism is destroyed [52]. Under adverse circumstances, neutrophil can release proteinases through microbursts, to the extracellular space, or produce NETs to fix the microorganisms, stop their migration, and concentrate on toxic factors [56].…”
Section: Neutrophilsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereafter, cytoplasmic granules in the neutrophil get fused with the phagolysosome where the microorganism is destroyed [52]. Under adverse circumstances, neutrophil can release proteinases through microbursts, to the extracellular space, or produce NETs to fix the microorganisms, stop their migration, and concentrate on toxic factors [56].…”
Section: Neutrophilsmentioning
confidence: 99%
“…Cellular cytotoxic role in cancer is traditionally associated with cytotoxic T cells, NK cells, and macrophages, and little attention is focused on neutrophils, but nowadays, reports are linking neutrophils to different stages of cancer [56]. Naïve neutrophils are recruited to the tumor, mainly by macrophages, and display the same repertory to kill a microorganism for the destruction of a tumor cell, and eventually a pro-host or pro-tumoral effect in situ is developed (Figure 2) [52].…”
Section: Neutrophilsmentioning
confidence: 99%
“…Although the exact mechanism remains unknown, NETs have been described to trigger thrombogenicity and this phenomenon could be explained by neutrophils themselves and histone release but also due to the platelet trapping by NETs and the initiation of the formation of the thrombus 2,8 . In addition, some elements of NETs might induce platelet activation, accumulation of erythrocytes, and the release of von Willebrand factor, which is known as one of the main components of thrombus 8 . In vitro studies have shown that venous thrombi could be significantly reduced when NETs were targeted with NE inhibitor and DNAse I.…”
Section: Nets and Cancermentioning
confidence: 99%
“…In vitro studies have shown that venous thrombi could be significantly reduced when NETs were targeted with NE inhibitor and DNAse I. Furthermore, data suggest that leukemia and cancer cells produced factors contributing to the formation of NETs, which were at the same time a predisposition for thrombosis 2,8 . The different currently accepted roles of NETs in cancer are summarized in figure 1.…”
Section: Nets and Cancermentioning
confidence: 99%
“…On the other hand, NET can promote migration and immune avoidance of tumor cells. The possible role of the flow of neoplastic process As a prognostic biomarker in NET is suggested [4,5]. The aim of this study was to investigate extracellular neutrophil traps in colorectal cancer.…”
mentioning
confidence: 99%